2016
DOI: 10.5194/hess-2016-21
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sharing water and benefits in transboundary river basins

Abstract: Abstract. The equitable sharing of benefits in transboundary river basins is necessary to solve disputes among riparian countries and to reach a consensus on basin-wide development and management activities. Benefit sharing arrangements must be collaboratively developed to be perceived not only as efficient, but also as equitable in order to be considered acceptable to all riparian countries. The current literature mainly describes what is meant by the term benefit sharing in the the context of transboundary r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The conflicts around the utilization of the Nile water resources persists due to the treaty of 1959 which led to the signing of Cooperative Framework Agreement (CFA) by a number of the Nile basin countries, with the notable exceptions of Egypt, Sudan and South Sudan [ 67 ]. The CFA was signed between 2010 and 2011 and establishes the principle that each Nile Basin state has the right to use, within its territory, the waters of the Nile River Basin, and lays down some factors for determining equitable and reasonable utilization such as the contribution of each state to the Nile waters and the proportion of the drainage area [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…The conflicts around the utilization of the Nile water resources persists due to the treaty of 1959 which led to the signing of Cooperative Framework Agreement (CFA) by a number of the Nile basin countries, with the notable exceptions of Egypt, Sudan and South Sudan [ 67 ]. The CFA was signed between 2010 and 2011 and establishes the principle that each Nile Basin state has the right to use, within its territory, the waters of the Nile River Basin, and lays down some factors for determining equitable and reasonable utilization such as the contribution of each state to the Nile waters and the proportion of the drainage area [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the resulting operation might involve benefits asymmetrically distributed among the stakeholders in the basin, creating equity issues. Benefit-sharing mechanisms could be implemented to compensate for equity issues [Arjoon et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by Sadoff and Grey (2002), it is critical to understand and account for the range of inter-related benefits resulting from the development of international rivers in a cooperative way. Such cooperation of water resources development in international river basins has been widely investigated in recent years (Li et al, 2019;Luchner et al, 2019;Anghileri et al, 2013;Uitto and Duda, 2002;Dombrowsky, 2009;Tilmant and Kinzelbach, 2012;Arjoon et al, 2016;Wu and Whittington, 2006;Wheeler et al, 2018;Goor et al, 2010;Degefu et al, 2016). For example, Arjoon et al (2016) proposed a benefit-sharing method based on the optimization results from a hydro-economic model and evaluated the value of cooperative water management in the Eastern Nile River basin; Li et al (2019) analyzed the water benefits of stakeholders from transboundary cooperation under different reservoir operation scenarios by using cooperative game theory methods; Luchner et al (2019) simulated reservoir operations and water allocation in an international river basin in Central Asia and found that international cooperation in the power sector can ease the conflict between upstream hydropower production and downstream irrigated agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Although cooperation in transboundary river basins can result in a win-win situation for both downstream and upstream stakeholders, cooperative water use strategies are obstructed by single-sector interests, especially when long-term commitments are involved (Wu and Whittington, 2006 specifically, it is often difficult to achieve a mutually agreed-on cooperation strategy given divergent solution preferences by stakeholders. Additionally, there is no standard that regulates how the benefits of water use from various sectors (e.g., drinking, agriculture, industry, recreation, and navigation) are quantified and what mechanism should be used to allocate/share the benefits (Arjoon et al, 2016;Acharya et al, 2020). Thus, most previous studies focus on evaluating the impact of cooperative operation in transboundary river basins and illustrating the importance of a cooperative strategy through water system optimization and simulation (Goor et al, 2010;Anghileri et al, 2013;Uitto and Duda, 2002;Dombrowsky, 2009;Tilmant and Kinzelbach, 2012;Luchner et al, 2019).…”
Section: Introductionmentioning
confidence: 99%